Pengaruh Faktor End User Computing Satisfaction (EUCS) Terhadap Manfaat Nyata Pengguna Sistem Informasi Elektronik (E-Puskesmas) di Puskesmas Sawah Besar Jakarta - Hera Adrianti; Hosizah Usman (Indonesian of Health Information Management Journal (INOHIM), 2018)
AbstractEnd User ComputingSatisfaction (EUCS) is a way to carry out an assessment of the satisfaction of an information system covering the content, format, accuracy, timeliness, and ease of use. User satisfaction is crucial to the success of the system as well as the effect on the net benefits. The net benefit was assessed by the effects of the work, efficiency, effectiveness, and reducing errors. Most users are not satisfied due to the implementation of an electronic information system (e-PHC) in Sawah Besar Jakarta Health Center is often an error occurs, the patient visit reports are inconsistent, there is no warning if there is a similarity of patient identity and the process of bridging the BPJS rudimentary application. The purpose of this study to determine the effect End User Computing Satisfaction (EUCS) against net benefit users of Electronic Information System (e-PHC) in Sawah Besar Jakarta Health Center. This study uses a quantitative approach with survey observational and cross-sectional design. The study population is 84 and sample 46 users of e-health center comprising 10 nurses, midwives 9, 10 doctors, 9 PMIK, 5 pharmaceutical and 3 nutritionists. Collecting data using questionnaires, data analysis simple linear regression. Results of simple linear regression test showed that there is significant effect between the factors of End User Computing Satisfaction (EUCS) against the net benefit users of electronic information system (e-PHC) in Sawah Besar Jakarta Health Center (p-value 0.000 <0.05) with a net benefit equation = 4.093 + 0.292 (factor EUCS). The net benefit of  if the factor 4.093EUCS = 0, whereas if there is additional 1 EUCS factor value then the net benefits = 4.093 + 0.292.Keywords: end user computing satisfaction (EUCS), net benefits, e-health center AbstrakEnd User Computing Satisfaction (EUCS) merupakan cara untuk melakukan penilaian atas kepuasan terhadap sebuah sistem informasi meliputi content, format, accuracy, timeliness, dan ease of use. Kepuasan pengguna sangat menentukan dalam keberhasilan sistem serta berpengaruh terhadap manfaat nyata. Manfaat nyata dinilai dengan efek pekerjaan, efisiensi, efektivitas, dan pengurangan kesalahan. Sebagian pengguna merasa tidak puas dikarenakan penerapan sistem informasi elektronik (e-Puskesmas) di Puskesmas  Sawah Besar Jakarta sering terjadi error, laporan kunjungan pasien tidak konsisten, tidak ada warning jika ada kesamaan identitas pasien, dan proses bridging dengan aplikasi BPJS belum sempurna. Tujuan penelitian ini untuk mengetahui pengaruh faktor End User Computing Satisfaction (EUCS) Terhadap Manfaat nyata pengguna Sistem Informasi Elektronik (e-Puskesmas) di Puskesmas Sawah Besar Jakarta. Penelitian ini menggunakan pendekatan kuantitatif dengan survey observasional, dan desain cross sectional. Populasi penelitian ini 84 dan besar sampel 46 pengguna e-Puskesmas terdiri 10 perawat, 9 bidan, 10 dokter, 9 PMIK, 5 farmasi dan 3 ahli gizi. Pengumpulan data menggunakan kuesioner, analisis data regresi linear sederhana. Hasil uji regresi linear sederhana diperoleh bahwa ada pengaruh signifikan antara faktor End User Computing Satisfaction (EUCS) terhadap manfaat nyata pengguna sistem informasi elektronik (e-Puskesmas) di Puskesmas Sawah Besar Jakarta (p-value 0,000<0,05) dengan persamaan manfaat nyata = 4,093 + 0,292 (Faktor EUCS). Manfaat nyata sebesar 4,093 jika faktor EUCS=0, sedangkan jika terjadi penambahan 1 nilai faktor EUCS maka manfaat nyata = 4,093 + 0,292.Kata Kunci: end user computing satisfaction (EUCS), manfaat nyata, e-puskesmas